Histories of economic thought - Biddle, Jeff; Samuels, Warren J., 1933- (Research in the history of economic thought and methodology ;, 2003)
Four documents pertinent to the history of economic thought are published for the first time: a list of references in economics dating from 1880; a syllabus of lectures on the history of economics given by C.H. Hull in Cornell University in 1895; the outlines for Walton H. Hamilton's Principles-of Economics course in the University of Michigan, 1911; and notes taken in James S. Earley's course on the Development of Economics, 1954-1955, by Warren J. Samuels.